The Development of a Space Climatology: 2. The Distribution of Power Input Into the Magnetosphere on a 3‐Hourly Timescale. Issue 1 (30th January 2019) - Lockwood, Mike; Bentley, Sarah N.; Owens, Mathew J.; Barnard, Luke A.; Scott, Chris J.; Watt, Clare E.; Allanson, Oliver; Freeman, Mervyn P.
Abstract: Paper 1 in this series (Lockwood et al., 2018a, https://doi.org/10.1029/2018SW001856 ) showed that the power input into the magnetosphere P α is an ideal coupling function for predicting geomagnetic "range" indices that are strongly dependent on the substorm current wedge and that the optimum coupling exponent α is 0.44 for all averaging timescales, τ, between 1 min and 1 year. The present paper explores the implications of these results. It is shown that the form of the distribution of P α at all averaging timescales τ is set by the interplanetary magnetic field orientation factor via the nature of solar wind‐magnetosphere coupling (due to magnetic reconnection in the dayside magnetopause) and that at τ  = 3 hr (the timescale of geomagnetic range indices) the normalized P α (divided by its annual mean, that is, < P α  > τ =3hr /< P α  > τ =1yr ) follows a Weibull distribution with k of 1.0625 and λ of 1.0240. This applies to all years to a useful degree of accuracy. It is shown that exploiting the constancy of this distribution and using annual means to predict the full distribution gives the probability of space weather events in the largest 10% and 5% to within uncertainties of magnitude 10% and 12%, respectively, at the one sigma level. Plain Language Summary: This is another step toward constructing a climatology describing the statistics of how space weather has varied over the past 400 years. This climatology will be valuable in the design of systems vulnerable to space weather. Previous work has showed that the probability of an event of a given magnitude occurring in any 1 year can be predicted from average activity levels in that year. This is an approximate but extremely valuable result that helps us understand the occurrence of events before the space age—however, it is a result that would be more valuable and could be used with greater confidence if we understood why it applies. This paper provides us with that understanding. Key Points: The normalized distribution of power input to the magnetosphere is set by IMF orientation variability via magnetopause reconnection rate The 3‐hourly normalized power input obeys a Weibull distribution with shape parameter 1.0625 and scale parameter 1.0240 for all years Annual means can give the probability of space weather events in the largest 10% and 5% to within one sigma errors of 10% and 12%, respectively